2020
DOI: 10.3390/s20205799
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Response and Residual Thermal Stress of Metal-Core Piezoelectric Fiber /Al Matrix Composites

Abstract: It is well known that the curing residual stress induced during a fabrication process has a great influence on the performance of piezoelectric composite devices. The purpose of this work was to evaluate the residual thermal stress of lead zirconate titanate piezoelectric fiber aluminum (Al) matrix (piezoelectric fiber/Al) composites generated during fabrication and to understand the effect of the residual thermal stress on the electromechanical response. The three-dimensional finite element method was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, polymethyl methacrylate (PMMA) based PZTs flexible composite films have been fabricated by a solvent evaporation technique, and the results showed that the composites are suitable, potential, and functional candidates for energy harvesting applications [ 8 ]. In our previous study, embedding a PZT hollow fiber into an aluminum matrix not only enhanced the mechanical performance, but also improved the piezoelectricity of the PZT composites due to the high residual stresses of the PZT fiber [ 9 ]. Many studies have proved that PZTs are prospective materials for building a dynamic detection system, and FEA is a potential method to further optimize the design of detecting viruses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, polymethyl methacrylate (PMMA) based PZTs flexible composite films have been fabricated by a solvent evaporation technique, and the results showed that the composites are suitable, potential, and functional candidates for energy harvesting applications [ 8 ]. In our previous study, embedding a PZT hollow fiber into an aluminum matrix not only enhanced the mechanical performance, but also improved the piezoelectricity of the PZT composites due to the high residual stresses of the PZT fiber [ 9 ]. Many studies have proved that PZTs are prospective materials for building a dynamic detection system, and FEA is a potential method to further optimize the design of detecting viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric ceramics and polymers are expected to exhibit sensing and energy harvesting properties, and many studies have focused on this possibility [ 3 , 4 , 5 , 6 , 7 , 8 ]. In addition, magnetostrictive alloys are considered promising energy harvesting materials [ 9 , 10 ], and hence the development and characterization of such alloys have attracted attention [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties are utilized in applications such as impact detection [19] and viscosity sensor [20,21]. The robustness of PZT/Al composites is attributed to the presence of a metal matrix and the extremely high compressive stresses generated during the embedding process [22,23]. These stresses originate from the difference in thermal expansion coefficients of the piezoelectric ceramic fibers and metal.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the application of compressive stress to polarized ceramics have been reported [27][28][29]; however, most of these studies reported the change in piezoelectric properties and polarization under uniaxial compressive stress [30,31]. Few studies have been conducted on the polarization state and the piezoelectric properties under extremely high triaxial stress (about 1 GPa [22,23]), such as the PZT embedded in aluminum.…”
Section: Introductionmentioning
confidence: 99%